Ammonia ((14)C-Methylamine) Transport across the Bacteroid and Peribacteroid Membranes of Soybean Root Nodules - Udvardi, Michael K. (1990)
[(14)C]Methylamine (MA; an analog of ammonia) was used to investigate ammonia transport across the bacteroid and peribacteroid membranes (PBM) from soybean (Glycine max) root nodules. Free-living Bradyrhizobium japonicum USDA110 grown under nitrogen-limited conditions showed rapid MA uptake with saturation kinetics at neutral pH, indicative of a carrier. Exchange of accumulated MA for added ammonia occurred, showing that the carrier recognized both NH(4)(+) and CH(3)NH(3)(+). MA uptake by isolated bacteroids, on the other hand, was very slow at low concentrations of MA and increased linearly with increasing MA concentration up to 1 millimolar. Ammonia did not inhibit MA by isolated bacteroids and did not cause efflux of accumulated MA. PBM-enclosed bacteroids (peribacteroid units [PBUs]) were qualitatively similar to free bacteroids with respect to MA transport. The rates of uptake and efflux of MA by PBUs were linearly dependent on the imposed concentration gradient and unaffected by NH(4)Cl. MA uptake by PBUs increased exponentially with increasing pH, confirming that the rate increased linearly with increasing CH(3)NH(2) concentration. The results are consistent with other evidence that transfer of ammonia from the nitrogen-fixing bacteroid to the host cytosol in soybean root nodules occurs solely by simple diffusion of NH(3) across both the bacteroid and peribacteroid membranes.